Pengelolaan Unsur Sinematografi oleh Director of Photography pada Film Dokumenter “Mindful Sip: Matcha Beyond The Trend” - Aprilia Rachma; Dian Wardiana Sjuchro; Kokom Komariah (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2026)
The development of documentary films in Indonesia has encouraged the need for presenting reality in an informative manner while maintaining strong visual quality. Documentary films were no longer viewed merely as a medium for recording facts, but also as a creative medium capable of delivering social messages through a cinematic approach. Cinematography became an important element because it played a role in constructing meaning, atmosphere, and viewing experience through well-directed visual management. This study discussed the management of cinematographic elements by the Director of Photography in the documentary film “Mindful Sip: Matcha Beyond The Trend”, which raised the phenomenon of increasing matcha consumption as part of the lifestyle trend among young people. The method used was a creative approach based on expository documentary through the stages of pre-production, production, and post-production. The entire creation process was focused on concept planning, image capturing, and visual as well as narrative refinement so that the documentary message could be conveyed effectively. The results showed that matcha had developed into a symbol of a healthy, productive, and aesthetic lifestyle, yet awareness of responsible consumption was often neglected. The management of camera angle, camera movement, type of shot, and composition was proven to strengthen visual representation and help audiences understand the phenomenon more critically. Therefore, cinematography played an important role not only in producing attractive visuals, but also in clarifying the documentary’s message regarding the relationship between consumption trends and bodily experience.